(untitled) (Journal of Human Sciences, 2025)
The study of interpretation is no longer limited to historical approaches only; that is, starting from the reasons for revelation and stopping at the limits of the sciences of language and rhetoric, but rather systematic approaches have become a major role in approaching the Qur’anic text, so many diverse studies have emerged that examine the structure of the Qur’anic text, its style, its arguments, and its narration techniques. The latter is what we are on the way to, as the Qur’anic story has become an applied example of all narrative theories, the most important of which are the mystical narratives that this study has adopted as a research method. The research was divided into two main sections, the first theoretical and the other procedural, and the theoretical section included a presentation of the concept of understanding, cognitive narratives, and possible worlds. The applied aspect was also divided into two sections: the first is the worlds of vision in the Qur’anic text, and the other is the worlds of vision in the book Stories of the Prophets by Al-Tha’labi. This study yielded the most important results, the cognitive approach to narration contributes to a new understanding of the Qur’anic narration, and provides a scientific explanation for the diversity, multiplicity, and difference in the explanations of the Qur’anic stories.